2021
DOI: 10.1016/j.ijid.2020.11.143
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic risk of COVID-19 outbreak in the United States: An analysis of network connectedness with air travel data

Abstract: Highlights Time series plot of network density can serve as early detection of pandemic development. Pandemic progression can be tracked through the association of network density and air travel data. The application of network density on detection of the pandemic risk and its association with the air travel data may help optimize timely containment strategies to mitigate the outbreak of infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…Moreover, using the parameters obtained from our estimation, we examined the highest probability of two countries being linked, the country-specific effect, the initial average distance, and the speed to build up the pandemic risk. As in other papers [ 28 , 51 , 52 , 53 ], using this pandemic space analysis, we concluded that both lockdown and travel restrictions are effective at reducing the pandemic risk across countries. Nevertheless, these two measures, and probably also other control measures, are not sufficient to wipe out the risk of pandemic across countries.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, using the parameters obtained from our estimation, we examined the highest probability of two countries being linked, the country-specific effect, the initial average distance, and the speed to build up the pandemic risk. As in other papers [ 28 , 51 , 52 , 53 ], using this pandemic space analysis, we concluded that both lockdown and travel restrictions are effective at reducing the pandemic risk across countries. Nevertheless, these two measures, and probably also other control measures, are not sufficient to wipe out the risk of pandemic across countries.…”
Section: Discussionsupporting
confidence: 83%
“…One possible approach is to make use of the network statistics in pandemic network data [ 24 ]. There have been recent research papers published that propose the use of COVID-19 pandemic network data to predict and estimate the pandemic risk across countries [ 25 , 26 , 27 , 28 ]. The authors of those papers based their conclusions on the study of pandemic risk scores and network connectedness, using network density, the clustering coefficient, and the assortativity coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Although the direction of the relationship between daily flights and the number of cases varies between countries in the countries examined within the scope of the study, a statistically significant but quite weak relationship was found in all countries in general. However, although the results of the studies on the subject in the literature differ, the results of our study coincide with the results of Tiwari et al (2020).…”
Section: Demet Dağlı -Ednan Ayvazsupporting
confidence: 84%
“…( 2021b ), and Tiwari et al. ( 2021 ), we obtain the network densities for the pandemic networks according to the steps below. Let be the number of confirmed cases of country i in day t .…”
Section: Methodsmentioning
confidence: 99%
“…Using the methods in Chu et al ( 2020a , 2020b ), Tiwari et al. ( 2021 ), and So et al. ( 2021b ) who proposed the use of network density to detect early signals of the COVID-19 pandemic, we test any lead-lag relationships between the pandemic network and the financial network by testing the Granger causality between the pandemic network density and the financial network density.…”
Section: Introductionmentioning
confidence: 99%